Lupus erythematosus and lichen planus overlap syndrome: a case report with a rapid response to topical corticosteroid therapy - Gulsen Tukenmez Demirci; Ilknur Kivanc Altunay; Sezgi Sarikaya; Damlanur Sakiz (PAGEPress Publications, 2011)
Lupus erythematosus (LE) and lichen planus (LP) may occur as an overlap syndrome. We report the clinical characteristics of a young man with lesions diagnosed as LE and LP by histopathological and direct immunoflurosence examinations. We achieved remarkable clinical response from the treatment with topical corticosteroids and no recurrence was seen in a 6 months of follow up time. We found this case interesting because of the rapid improvement with corticosteroid and discussed if there is a real overlap or a coexistence according to the literature.